Advanced fabrication of complex biopolymer microcapsules via RSM-optimized supercritical carbon dioxide solution-enhanced dispersion: a comparative analysis of various microencapsulation techniques - Gholivand, Somayeh; Tan, Tai Boon; Mat Yusoff, Masni; Choy, Hew Weng; Teow, Shuh Jun; Wang, Yong; Liu, Yuanfa; Tan, Chin Ping (Elsevier, 2024)
This work aimed to enhance hemp seed oil encapsulation within a hemp seed protein-alginate complex by optimizing parameters in the solution-enhanced dispersion process, employing supercritical carbon dioxide (SEDS) without reliance on organic solvents or elevated temperatures. By response surface methodology (RSM), the microencapsulation efficacy (MEE), particle size (PS) and peroxide value (PV) was determined with respect to three parameters; temperature (°C), pressure (bar) and feed flow rate (mL/min). The optimum conditions were predicted at temperature (40 °C), pressure (150 bar) and feed flow rate (2 mL/min) to offer an MEE of 89.47%, PS of 7.81 μm and PV of 2.91 (meq/kg oil). In addition, the SEDS method was compared with spray- and freeze-drying for encapsulating hemp seed oil. The findings demonstrated SEDS' superiority, exhibiting exceptional attributes such as the highest MEE, smallest PS and the production of spherical, smooth microcapsules. This highlights its effectiveness in comparison to spray- and freeze-drying methods.